2016
DOI: 10.1021/acs.jpclett.6b01442
|View full text |Cite
|
Sign up to set email alerts
|

Universal Repulsive Contribution to the Solvent-Induced Interaction Between Sizable, Curved Hydrophobes

Abstract: In addition to the direct attraction, sizable hydrophobes in water experience an attractive force mediated by interfacial water. Using simple geometric arguments, we identify the conditions at which the water-induced interaction between curved hydrocarbon surfaces becomes repulsive. The repulsive contribution arises from the thermodynamic penalty due to the emergence of the liquid/vapor boundary created as water gets expelled between curved hydrophobes. By augmenting the mean field approach with atomistic simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 39 publications
5
17
0
Order By: Relevance
“…For convex surfaces, results in Fig. 1B are also in good agreement with those of Jabes et al (52), who found that hydration shell compressibility reduces by about 22% near a hydrocarbon-coated cylinder with κ = 1.13 nm −1 , relative to that near a flat plate. Our results highlight an asymmetric dependence of hydration shell compressibility on the sign of nanotube curvature.…”
Section: Resultssupporting
confidence: 89%
“…For convex surfaces, results in Fig. 1B are also in good agreement with those of Jabes et al (52), who found that hydration shell compressibility reduces by about 22% near a hydrocarbon-coated cylinder with κ = 1.13 nm −1 , relative to that near a flat plate. Our results highlight an asymmetric dependence of hydration shell compressibility on the sign of nanotube curvature.…”
Section: Resultssupporting
confidence: 89%
“…This success of macroscopic theory may seem surprising, given that the blocks we consider have the microscopic cross sectional area ≈10σ × 5σ. However, it is in keeping with recent simulation studies 6,8 of water induced interactions between hydrophobes. In contrast, when both blocks are solvophilic, the potential W (x G ) is oscillatory but overall repulsive and exhibits only a weak dependence on β∆µ; see Fig.…”
Section: Discussionsupporting
confidence: 85%
“…This can also be seen from the inset which shows the adsorption (10). Although Γ is somewhat larger in magnitude than that for the wall potential (8), displayed in the inset to Fig. 4, it remains finite at coexistence.…”
Section: B Single Soft Lennard-jones Wallmentioning
confidence: 60%
“…In practice, we varied wall while keeping the liquid properties constant and measured the corresponding contact angle, θ. We note that additional complexities that also influence the surface solvophobicity including functionalization and polarity effects can not be captured with our present model 38 .…”
Section: A Studied Systemmentioning
confidence: 82%
“…Along with the wetting properties of the solid, the role of its geometrical structure was also covered in several studies [37][38][39] . For example, Jabes et al recently demonstrated that using the same solid composition and size, qualitatively different solvent-mediated forces can be obtained only by changing the solid shape between fullerenes, nanotubes and graphene-like structures 38 . Altogether, this work is integrated to a general mean-field theory of hydrophobicity developed by Lum, Chandler and Weeks 40 and further refined in more recent publications 31,41,42 .…”
Section: Introductionmentioning
confidence: 99%